Pendampingan Guru Sekolah Dasar dalam Mengembangkan Bahan Ajar Berbasis Kearifan Lokal Sikka melalui Model Project Based Learning - Yufrinalis, Marianus; Tiring, Sri Sulystyaningsih Natalia Daeng; Putra, Sukarman Hadi Jaya; Gobang, Yonas Klemens Gregorius Dori; Fausta, Agustina; Rahel, Elisabeth Lusia (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Community Service Activities (PkM) in the form of workshops and mentoring to teachers at SDK 025 Kloangrotat, are based on the problems faced by teachers at the school. Most teachers only teach fixated on textbooks provided by the government. Teachers lack innovation and development of teaching materials, especially integrating the values of local wisdom of Sikka Regency into teaching materials. The purpose of this activity is to increase teachers understanding of the concept of developing teaching materials based on local wisdom and their skills in designing application-based teaching materials. The implementation method is in the form of socialization, training, and mentoring for teachers. The result of this activity is that all teachers can understand the concept of developing teaching materials based on local wisdom and are able to design their own teaching materials based on the Canva-Pro application. Activities can have a further impact by encouraging teachers to always develop their abilities while being accompanied continuously by instructors or learning experts.